Effects of Composition and Strength of Wheat Gluten on Starch Structure, Digestion Properties and the Underlying Mechanism - Xiaoyang Zou; Xiaolong Wang; Liang Li; Pai Peng; Qianying Ma; Xinzhong Hu; Rudi Appels (Foods, 2022)
To understand the effect of gluten on starch digestion characteristics, the structural characteristics of protein, starch, and starch digestion attributes were explored by using flours of four wheat near-isogenic lines. Protein and starch fractions from the four flours were used to form so-called recombinant flours where glutenin and gliadin protein fractions, in different ratios, were combined with starch and heated in a water slurry at 80 °C for 5 min. We found that starch digestibility of the recombinant flours could be reproducibly modified by altering the long- and short-range molecular order of starch through varying the attributes of the gluten protein by virtue of the gluten strength as well as the proportions of glutenin and gliadins. The gluten composition changes of strong-gluten flour did not improve the starch digestion resistibility, however, for the moderate- and weak-gluten flours, the proportional increase of glutenin improved the resistance of starch to digestion through the increased long- and short-range molecular order of starch. The resistance of starch to digestion could also be enhanced with increasing gliadin, and was associated with the modified short-range molecular order of starch. We propose that flour mixtures can be optimized for specified product quality by manipulating the amounts of both gliadin and glutenin.